Irreducible Water Saturation And Its Governing Factors: Characteristics Of Some Sandstones In Western Indonesia - Bambang Widarsono (Scientific Contributions Oil and Gas, 2011)
Irreducible water saturation (Swirr) plays a very significant role in the estimation of hydrocarbon in place and reserves. Inaccurate Swirr and lack of knowledge for judging its accuracy may result in erroneous and misleading reserve estimates along with its consequences. This study is basically aimed at understanding of Swirr characteristics of reservoir sandstones in some fields in western Indonesia. For the study, data obtained from 1,334 core samples – taken from 78 fields in 10 sedimentary basins – is used. Observations and investigations are made in sedimentary basin, field, and formation scales. The main finding is that rock wettability plays a very significant factor in determining Swirr characteristics, in a manner more than what rock pore types and configuration do. Its variation – be it contrasting or difference in strength – influences the Swirr characteristics in its relation to rock permeability. It is also found that geological similarity and geographical proximity do not have effects on Swirr characteristics unless they directly affect the rock’s overall wettability. This occurs not only at higher scale of sedimentary basin but also at lower levels of field and rock formations. The study also produces permeability - Swirr correlations for both sedimentary basins and rock formations levels. The overall results of this study is an understanding that gross simplification in assuming reservoir general wettability has to avoided in order to prevent erroneous picture over a field’s most representative Swirr characteristics.